PENINGKATAN KETERAMPILAN DAN KUALITAS PEMBELAJARAN MAHASISWA MELALUI PROGRAM INTERNSHIP DI SUJAYA PROCESSING FOOD SINGKAWANG - Habel, Habel; Valentinus, Valentinus; Dedy, Dedy (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2025)
Internship program skills and quality of student learning internship is an educational strategy to combine theory with practical work in the industrial world. This program aims to analyze the impact of internship programs on the development of skills and improving the quality of learning of students participating in PT Sujaya Processing Food, this internship program is a learning approach that combines theoretical knowledge with practical experience in the industrial work environment. This study shows that student internship programs can effectively develop student skills. This includes technical skills, such as operating production machines, quality control in the food industry, and a better understanding of industrial work systems. In addition, soft skills such as discipline in working, effective communication, and teamwork have increased significantly for students.